PROPAGASI BALIK MENENTUKAN PREDIKSI PRODUKSI USAHA SONGKET SILUNGKANG KOTA SAWAHLUNTO - Rima Liana Gema; Devia Kartika (Computer Based Information System Journal, 2018)
Artificial Neural Networks is a computational paradigm in which the way it works mimics the biological nerve cell system based on the characteristics of the function of the human brain. One method used in Artificial Neural Networks is a backpropagation algorithm that is widely used, especially in dealing with the problem of identification, prediction, recognition of complex patterns because this method is able to predict what will happen in the future based on patterns that existed in the past. Songket is one of the works of skilled hands of the original Silungkang craftsmen, Sawahlunto City, West Sumatra who have varied and unique patterns and motifs. Sawahlunto City Government, West Sumatra prioritizes the development of Silungkang songket craft business, which is a regional specialty, to enter the export market. At the initial stage, the regional government's priority is to increase the production of crafters by facilitating the development of micro, small and medium enterprises (MSMEs), especially those engaged in songket, to continue to be developed by improving quality and creativity. The city of Sawahlunto can help several parties such as the government, micro, small and medium enterprises in making good handling and decision making efforts to increase the production of Songket Silungkang MSMEs in Sawahlunto City.